Kukulcan's Realm : Urban Life at Ancient Mayapán - Masson, Marilyn A. (Book collections on Project MUSE., 2014)
Kukulkan's Realm chronicles the fabric of socioeconomic relationships and religious practice that bound the Postclassic Maya city of Mayapán's urban residents together for nearly three centuries. Presenting results of ten years of household archaeology at the city, including field research and laboratory analysis, the book discusses the social, political, economic, and ideological makeup of this complex urban center. Masson and Peraza Lope's detailed overview provides evidence of a vibrant market economy that played a critical role in the city's political and economic success. They offer new.